2010
DOI: 10.1021/ma1005638
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Mechanical Relaxation below the Glass Transition Temperature in Partially Supramolecular Networks

Abstract: Cross-linked polymers in which part of the covalent cross-links have been replaced by reversible cross-links have potential application in coatings with improved stress relaxation. Here we present a detailed study of materials based on copolymers of ε-caprolactone and L-lactic acid, containing different ratios of covalent and ureidopyrimidinone (UPy) dimer cross-links. Their thermal and mechanical properties were tested by differential scanning calorimetry (DSC), dynamic mechanical analysis (DMA), and dielectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 13 publications
1
35
0
Order By: Relevance
“…In a more general perspective, it will be interesting to explore the usefulness of the method when applied to other relevant systems like, for instance, network forming polymers. 8,9,47,48 This will deserve future investigations. 3,5,7,10,14,15,19,23,29,31,34,35,36,39,44,48,50,51,54,55,56,57,59, 60, 61, 62} along the N seg + 1 = 65 possible positions.…”
Section: Discussionmentioning
confidence: 95%
“…In a more general perspective, it will be interesting to explore the usefulness of the method when applied to other relevant systems like, for instance, network forming polymers. 8,9,47,48 This will deserve future investigations. 3,5,7,10,14,15,19,23,29,31,34,35,36,39,44,48,50,51,54,55,56,57,59, 60, 61, 62} along the N seg + 1 = 65 possible positions.…”
Section: Discussionmentioning
confidence: 95%
“…The uriedopyrimidinone unit has been incorporated in a number of self-assembling applications [44,104]. This type of approach could equally be included in this section or the next (physically bonded).…”
Section: Reversible Chemical Bondsmentioning
confidence: 99%
“…A schematic of the type of network that can be formed is presented in Figure 8.5. This unit has four hydrogen bonds, and a bond energy that varies from 44 to 50 kJ/mol, which is clearly intermediate between hydrogen bonding (typically 1-2 kJ/mol) and the low end of covalent bond energies (>150 kJ/mol) [104]. Networks based on these types of hydrogen-bonded structures are called supramolecular networks.…”
Section: Reversible Chemical Bondsmentioning
confidence: 99%
“…However, there are a few studies on polymer networks having both covalent and MHB cross-linkages. 18, 19 Wietor et al partially replaced covalent urethane cross-linkages formed by the reaction of a trihydroxy-terminated three-armed flexible aliphatic polyester and diisocyanate to UPy-based multiple hydrogen bonds. They found that the incorporation of the UPy units improves the mechanical strength.…”
Section: Introductionmentioning
confidence: 99%